Pengaruh Motivasi, Biaya, dan Pengetahuan Mahasiswa Tentang UU No. 5 Tahun 2011 Pada Minat PPak - Dewi, Kadek Ayu Riana; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 22 No 1 (2018)DO - 10.24843/EJA.2018.v22.i01.p03, 2018)
This research was aim to get empirical evidence about the effect of motivation, education cost,  and knowledge of accounting students about the Act Number 5 of 2011 on the interest to follow Profession of Accountant Education (PPAk). The respondents are students of nonregular program, Faculty of Economics and Business, University of Udayana, which is 170 students. The sample determined by purposive sampling technique. Data collection method was by survey. Data analysis using multiple linear regression. The results show that motivation, education cost, and knowledge of accounting students about the Act Number 5 of 2011 have positive effect on the interest to follow PPAk. The conclusion was that accounting students having high motivation of quality, carrer, economic, positive perception about education cost, and having good knowledge about the Act Number 5 of 2011, would prefer to have high interests to follow PPAk. Keywords: Motivation, Education Cost, Knowledge, Interest
Keywords: Motivation, Education Cost, Knowledge, Interest